GIBBERELLIN (GA3) CONCENTRATION AND SOAKING DURATION EFFECTS ON DURIAN SEED GROWTH (Durio zibethinus Murr.): PENGARUH KONSENTRASI GIBERELIN (GA3) DAN LAMA PERENDAMAN TERHADAP PERTUMBUHAN BENIH DURIAN (Durio zibethinus Murr.) - Belinda Putri Dwiyanti; Mimik Umi Zuhroh; Sulis Dyah Chandra (ROCE : Jurnal Pertanian Terapan, 2025)
This research aims to determine the optimal combination of GA3 concentration and soaking duration to improve durian seed growth. The research was conducted using a Factorial Randomized Complete Block Design (Factorial RCBD) with 2 treatments: the first factor is Gibberellin Concentration (K) which consists of 4 levels: 0 ppm (control), 100 ppm, 200 ppm, and 300 ppm. While the second factor is Gibberellin Soaking Duration consists of 3 levels: 12 hours, 24 hours, and 36 hours. The results showed that there was an interaction between gibberellin concentration and soaking duration on the parameters of shoot emergence (with the best result of 5.43 days) and the root weight (with the best result of 6.8 g).